Nanoribbon‐Structured Organo Zinc Phosphite Polymorphs with White‐Light Photoluminescence1. (2nd December 2014) - Huang, Hui‐Lin; Wang, Sue‐Lein
Abstract The first neutral organo zinc phosphites composed of 2.8 nm‐wide ribbons were obtained in pure phases and exhibit near‐white‐light photoluminescence (PL). By using the "mesitylene strategy", interesting polymorphism in the system of NTHU‐14 was discovered. The S‐shaped ribbons are arranged into R and L arrays, resulting in RLR and RRR stacking for two polymorphs. π–π interactions exist within each array and hydrogen bonding between adjacent arrays. Besides a common ligand‐based emission band at 410 nm, the PL curves of polymorphs 14‐α and 14‐β are distinctly different: 14‐α gave a defect‐based emission at 565 nm, whereas 14‐β primarily shows a π‐excimer‐based emission at 535 nm. Electron paramagnetic resonance (EPR) data disclosed that radical species exist in the reaction and that the two phases were growing from different environments. Based on these results, the origin of the 565 nm band can be ascribed to lattice defects, and one possible cause of 14‐β not showing noticeable yellow emission is identified.